Distributional Effects of Growth and Public Expenditures in Africa: Estimates for Tanzania and Rwanda. (July 2017) - Almanzar, Miguel; Torero, Maximo
Highlights: Mean expenditure growth benefits the top quintiles of the expenditure distribution. Mean expenditure growth is not pro-poor and inclusive in Rwanda and Tanzania. The fiscal sector does not contribute to increase equity among the households. Public expenditures concentrate growth toward the middle of the distribution. Summary: In this paper we explore the effects of fiscal policies and growth on measures of household welfare across the distribution of expenditures for two African countries: Rwanda and Tanzania. We explore the effect of government expenditures on expenditure growth in each quintile of the expenditure distribution and the effect of growth for each group. We find that the benefits of growth are concentrated among the better-off sectors of the population in these two countries (perhaps to the detriment of the poorer sectors) by looking at the effects within a country and across different groups of households and administrative entities. We exploit variation in expenditures and growth across and within regions of each country to estimate the elasticities of expenditure with respect to fiscal expenditure and mean expenditure growth at different points of the expenditure distribution, using household survey data and government expenditure data at the district level. We find that, overall, mean expenditure growth benefits the top expenditure groups. The welfare spillovers are mostly present for top 20% of the expenditure distribution, with the middle of the distribution in Tanzania responding slightly to these spillovers. Public/social expenditures do not appear to affect inequality considerably, but do tend to work toward decreasing inequality. However, mean expenditure growth is related to increases in inequality in the sense that the richest sectors of the population benefit the most from growth. We find that the growth elasticity of expenditure is only above one for the top quintile in both countries. In Tanzania, a 1% increase in average household expenditure is related to a 1.96% expenditure growth in the top quintile and 0.43% in the third quintile. In Rwanda, a 1% increase in average household expenditure is related to a 1.93% increase in household expenditure in the top 20% of the distribution.